Novel‐graded traumatic brain injury model in rats induced by closed head impacts. Issue 5 (5th September 2018) - Wang, Hao; Zhu, Xiyan; Liao, Zhikang; Xiang, Hongyi; Ren, Mingliang; Xu, Minhui; Zhao, Hui
Abstract : Traumatic brain injury (TBI) is a leading cause of death and disability worldwide. Due to the heterogeneity of human TBI, none of the available animal models can reproduce the entire spectrum of TBI. This study was designed to develop a novel‐graded TBI rat model which is induced by closed head impacts (CHI) with reproducible brain damage and neurological dysfunction. A total of 75 male Sprague–Dawley rats (200 ± 20 g) were randomly equally divided into five groups: the Sham, 0.5, 0.6, 0.7 and 0.8 MPa groups. A custom‐made, air‐driven injury apparatus was used to induce CHIs (from 0.5 to 0.8 MPa). The kinematic parameters during the procedure were recorded by a force sensor and a high‐speed camera. Mortality rate, duration of unconsciousness (latency period of righting reflex), modified neurological severity score (mNSS) and whole brain water content (BWC) were examined. Pathological changes were evaluated by hematoxylin‐eosin (HE) stain and immunohistochemical stain for amyloid precursor protein (APP). The impact force and speed were 785.3 ± 14.12 N and 5.71 m/s in the 0.5 MPa group, 837.72 ± 10.41 N and 6.06 m/s in the 0.6 MPa group, 857.65 ± 11.11 N and 6.25 m/s in the 0.7 MPa group, and 955.6 ± 16.35 N and 6.67 m/s in the 0.8 MPa group. The periods of loss of righting reflex in 0.6–0.8 MPa groups were significantly higher than that in the Sham group. The mNSS score and BWC of the 0.8 MPa group remained higher 24 h after injury than other groups. Brain damage was indicated by increased APP expression in TBI rats. In conclusion, the newly developed CHI rat model was a highly controlled and reproducible graded TBI model, and provided a useful tool to investigate the underlying mechanism and therapeutic effects of TBI with various injury severities.